TINDAK PIDANA KEALPAAN BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 - Siti Rahmah (JURNAL HUKUM DAS SOLLEN, 2018)
Forgiveness is a violator of the law ban, but he does not heed the ban. He is negligent, negligent, careless in carrying out these actions. so, in the negligence of the defendant not heeding the prohibition so that he is not careful in carrying out an act that is causally objective to cause a condition that is prohibited from negligence which contains two conditions, namely not making estimators as required by law and not exercising caution as required by lawKeywords: Crime, Forgiveness This law regulates the principles and objectives of traffic, guidance, infrastructure, terminals, vehicles, drivers, insurance, transportation and criminal provisions. Article 27, states that: "Drivers of motorized vehicles involved in traffic accidents must stop vehicles, help people who are victims of accidents and report such accidents to State Police officials of the Republic of Indonesia